2017
DOI: 10.22616/foodbalt.2017.014
|View full text |Cite
|
Sign up to set email alerts
|

Facilities of bread enrichment with calcium by using eggshell powder

Abstract: Today's food ration does not often contain enough vitamins, fibre, macro-and micronutrients, especially calcium. Research aim: to study possibilities for the use of the eggshell powder in the production of bread enriched with calcium. For the study, the free-range hen eggshells, main components of which are inorganic salts, were used. The eggshells have been washed, dried and ground. To avoid changes in the texture of bread, the solubility of the eggshell powder was tested by incorporating different quantity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…This led to an increase in the calcium to phosphorus ratio which is in favour of increased calcium utilisation in humans (Makai and Chudáček 1991). Such data coincide with Ray et al (2017) and Bradauskiene et al (2017) studies as they also found a great increase in the calcium level of bakery products upon eggshell addition.…”
Section: Resultssupporting
confidence: 91%
“…This led to an increase in the calcium to phosphorus ratio which is in favour of increased calcium utilisation in humans (Makai and Chudáček 1991). Such data coincide with Ray et al (2017) and Bradauskiene et al (2017) studies as they also found a great increase in the calcium level of bakery products upon eggshell addition.…”
Section: Resultssupporting
confidence: 91%
“…Highest ash content (1.04%) was found in T 3 followed by T 2 (0.94%) while, lowest value (0.54%) was reported in T o . Present observations are in conformity with Bradauskiene et al (2017) as well as Ali et al (2019), who have established an increase in moisture and ash levels of product by augmenting the chicken eggshell powder.…”
Section: Effect Of Fortificant On Nutrient Compositionsupporting
confidence: 93%
“…In another study, Bradauskiene et al (2017) studied the possibility for the enrichment of chicken eggshell powder (ESP) at 0, 2.5, 5.0, 7.5, 10.0, 12.5 g in bread making. Sensory assessment of bread exhibited improved overall acceptability than control although, taste and flavor was alike or became worse.…”
Section: Organoleptic Properties Of Breadmentioning
confidence: 99%
“…The highest overall acceptability score were observed in eggshell fortified muffins in T0 control (7.6) followed by T3 with 8% calcium carbonate (7.5) and the minimum overall acceptability was observed in T2 with 16% eggshell powder (Table 5). The better flavor, color and overall acceptability was found in the bread with eggshell powder (ESP) as compared to control bread; though the taste and flavor stayed alike or became inferior as reported by [47].…”
Section: Sensory Evaluationmentioning
confidence: 94%